2016
DOI: 10.5713/ajas.16.0512
|View full text |Cite
|
Sign up to set email alerts
|

Volatile compounds and some physico-chemical properties of pastırma produced with different nitrate levels

Abstract: ObjectiveThe aim of the study was to evaluate the effects of different nitrate levels (150, 300, 450, and 600 ppm KNO3) on the volatile compounds and some other properties of pastırma.MethodsPastırma samples were produced under the controlled condition and analyses of volatile compounds, and thiobarbituric acid reactive substances (TBARS) as an indicator of lipid oxidation, non-protein nitrogenous matter content as an indicator of proteolysis, color and residual nitrite were carried out on the final product. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 20 publications
9
20
0
Order By: Relevance
“…A total of 45 volatile compounds, including alcohols, aldehydes, ketones, aliphatic and aromatic hydrocarbons, terpenes, sulphur compounds, esters, furans, nitrogenous compounds, were identified in pastırma samples. Similarly, in previous studies, compounds such as esters, aliphatic and aromatic hydrocarbons, sulphur compounds, alcohols, aldehydes, ketones, terpenes and furans have been identified in pastırma (Akköse et al, ; Kaban, ; Kaban & Kaya, ).…”
Section: Resultssupporting
confidence: 62%
See 4 more Smart Citations
“…A total of 45 volatile compounds, including alcohols, aldehydes, ketones, aliphatic and aromatic hydrocarbons, terpenes, sulphur compounds, esters, furans, nitrogenous compounds, were identified in pastırma samples. Similarly, in previous studies, compounds such as esters, aliphatic and aromatic hydrocarbons, sulphur compounds, alcohols, aldehydes, ketones, terpenes and furans have been identified in pastırma (Akköse et al, ; Kaban, ; Kaban & Kaya, ).…”
Section: Resultssupporting
confidence: 62%
“…Alcohols significantly contribute to the aroma of dry cured meat products due to their low odor threshold values (Kaban, , ; Lorenzo, ; Lorenzo & Carballo, ). Akköse et al () also found only 3,5‐octadiene‐2‐ol as alcohol in pastırma and reported that nitrate level had no significant effect on this compound. On the other hand, 15 compounds in the alcohol group were determined in dry cured bacon (Wu et al, ).…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations